Development Of An Online Consultation Information Service System At The Directorate General Of Mineral And Coal - Syamsul Rizal; Ito Riris Immasari; Anton Zulkarnain Sianipar (International Journal Labs, 2025)
In the era of digitalisation, public information services are a crucial aspect in supporting transparency and accountability in government agencies. The Directorate General of Mineral and Coal still faces several obstacles in delivering information services, including a limited number of face-to-face service staff and the absence of an efficient feedback system. Therefore, this study aims to develop an online consultation information system to improve service efficiency and flexibility. The system was developed using the RAD software development method, which includes the stages of needs analysis, system design, coding, and testing. The implementation was carried out using the PHP programming language with the CodeIgniter framework and MySQL database. A key feature of the system is real-time queue monitoring for business entities, which represents a novelty compared to previous research. System testing was conducted using black box and User Acceptance Testing (UAT) methods, involving employees and business representatives as end users. The results show that the system functions well according to user needs and is expected to enhance the quality of public information services at the Directorate General of Mineral and Coal.